The European metropolitan region of Zurich - a cluster of economic clusters? - Patrick Dümmler; Alain Thierstein (European Regional Science Association (ERSA), 2002)
Switzerland is a small country and possesses only two or three major economic regions of a metropolitan character. From a Swiss perspective the most important region is the European Metropolitan Region of Zurich (EMRZ). The EMRZ covers the whole of the Zurich economic area as well as adjacent areas like Zug, Lucerne and Basel. In empirical terms the EMRZ shows an above average percentage share of manufacturing industries and advanced service companies. Although the EMRZ is recognised as the prime Swiss economic engine there is only vague perception about the locational situation of its more important industries such as pharmaceuticals, machinery, financial services and others. A true-type cluster analysis for the EMRZ is still lacking. This deficit of fundamental knowledge about the region seems all the more important since several economic promotion agencies market the greater Zurich economic area as a region with clusters in financial service industries and medical equipment. The paper thus presents in a first step the EMRZ delimitation using some selected statistical data which are put into relation with the whole of Switzerland. The emphasis of this analysis lies on the identification of the major manufacturing and service industries that are located within the EMRZ. Followed by a short overview of the different cluster theories and a working definition for an empirical cluster analysis. The next section produces a cluster analysis based on data from the Swiss Federal Office of Statistics. This results in the identification of major clusters, locational coefficients as well as a first glimpse at the interrelations between selected clusters. The paper finishes off with a hypothesis whether the spatial proximity of economic clusters in the case of the EMRZ bears any causality with its economic development. Key words: cluster analysis, European metropolitan region of Zurich, regional innovation system, spillovers
Keywords: 330